Fossil Fuel Subsidy and Pricing Policies : Recent Developing Country Experience - Kojima, Masami (World Bank, Washington, DC, 2016)
The steep decline in the world oil price in the last quarter of 2014 slashed fuel price subsidies. Several governments responded by announcing that they would remove subsidies for one or more fuels and move to market-based pricing with full cost recovery. Other governments took advantage of low world prices to increase taxes and other charges on fuels. However, the decision to move to cost recovery and market prices, ending budgetary support, has not been implemented consistently across countries. Policy announcements have varied in the way they were communicated and the level of detail provided. When petroleum product prices bounced back during the first half of 2015, some reforming governments failed to raise prices correspondingly. Recent experience suggests that regular and frequent price adjustments, however small—as in Jordan and Morocco—help the government and consumers to get accustomed to fluctuations in world fuel prices and exchange rates. By contrast, freezing prices, even for a few months—for socioeconomic considerations or because the needed adjustments are small enough to be absorbed—increases the risk of reversion to ad hoc pricing and price subsidies. The more formally the decision to move to market-based pricing is communicated, the more public new price announcements, and the higher the frequency of price changes, the more likely the implementation of the announced pricing policy reform will be sustained.